Potassium channels in cancer: from hallmarks to therapeutic targeting - Yi-ling Zhang; Rong-jia Shi; Xin-hua Liang (Journal of Physiology and Biochemistry, 2026)

DA-MOT: a directed-angle-aware multi-object tracking framework for dairy cows - Tonghui Wu; Rong Wang; Haiyan Song; Zhiyong Zhang; Qifeng Li; Zhaoyang Wang; Yan Shi; Ronghua Gao (Computers and Electronics in Agriculture, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Foraminiferal composition of the early Oligocene Globigerinid-rich limestone in the Baiyun Sag, Pearl River Mouth Basin, and its paleo-environmental significance - Guang-Rong Peng; Cui Shi; Xiao-Ping Li; Xin-Yu Liu; Le-Yi Xu; Kai Zhang; Qi-Mei Guo; Bao-Hua Li (Palaeoworld, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Field measurements of the structural response of a linked twin-tower super-tall building during two typhoons - Liang Han; An Xu; Jiyang Fu; Yangxue Wang; Hua Rong; Wei Shi; Lele Zhang (Engineering Structures, 2026)

Dynamic modeling and numerical simulation of dense particle multiphase flows in resonant acoustic mixing - Jingming Zhang; Mingming Shi; Bao Rong; Gouping Wang; Da Li; Xiaoting Rui (Chemical Engineering Journal, 2026)

Endoplasmic reticulum stress-mediated glycophagy drives macrophage M1 polarization in silica nanoparticles-induced pulmonary fibrosis - Lei Bao; Zihan Geng; Linpeng Niu; Lili Shi; Liyi He; Yaxian Pang; Cunhui Zhang; Yan Liu; Jiawei Chen; Beibei Shi; Ruiting Wu; Jingyuan Wang; et al. (Journal of Environmental Sciences, 2026)

Denitrification-enhanced anaerobic digestion for stable synergy of hydrolysis and methanogenesis of N, N-dimethylformamide by nitrate addition: Delayed stimulation effect for successful enrichment of functional microorganisms - Junjie Zhou; Zhihao Shi; Tao Zhang; Yao Xu; Yong Hu; Chao Rong; Dapeng Li; Yu-You Li; Zhe Kong (Environmental Research, 2026)

An inflammation-targeted hydrogel for the synergistic treatment of colorectal cancer and associated neuropsychiatric dysfunction - Keying Chen; Na Li; Anni Ren; Lingling Yang; Pei Xie; Yong Gao; Yanwu Li; Ying Tang; Rong Zhang; Huafeng Pan; Bangjiang Fang; Tongkai Chen; et al. (Chemical Engineering Journal, 2026)

Solar-driven green degradation of lignin toward sustainable aromatics via BiVO4/Zn4In2S7 S-scheme heterojunction - Qunshuai Li; Luxin Zhang; Weiwei Shi; Sishang Ge; Menglu Hu; Rong Chen (Chemical Engineering Journal, 2026)

Callosobruchus maculatus feeding triggers multilevel defenses in cowpea seeds: from germination regulation to defensive metabolite biosynthesis - Hainuo Hong; Ming Zhang; Jiamei Geng; Qiulin Chen; Zheyi Shi; Yang Gao; Ying Zhou; Zeng‑Rong Zhu (Journal of Pest Science, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Fine mapping and candidate gene analysis of tassel glume closure1 (tgc1) gene in maize (Zea mays L.) - Ziwen Shi; Jinmiao Qin; Sheng Zhang; Yujiao Gao; Qing He; Hongyang Yi; Tingzhao Rong; Moju Cao (Theoretical and Applied Genetics, 2026)

Retraction notice to “Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study” [Sci. Total Environ. 883 (2023) 163662] - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Polystyrene nanoplastics induce neuroinflammation-driven depression-like behaviors in mice via the HIF-1α–NAT10–ac4C-mediated glycolytic activation - Yan Liu; Linpeng Niu; Cunhui Zhang; Lei Bao; Mengruo Wang; Qingping Liu; Hao Liu; Zhaohui Hu; Lili Shi; Yaxian Pang; Rong Zhang; Yujie Niu (Journal of Environmental Sciences, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

A Survey of the Species Origins of Common Fish Cell Lines—With a Particular Focus on the Grass Carp Ovarian Cell Line ( GCO ) - Hong Yang; Mijuan Shi; Yingyin Cheng; Wanting Zhang; Bin Gui; Rong Huang; Yaping Wang; Xiao‐Qin Xia (Journal of Fish Diseases, 2026)
Cell line misidentification or contamination undermines the reliability of research outcomes. In this study, we verified the species origin of commonly used fish cell lines, with a particular focus on the grass carp ovarian cell line (GCO). RNA‐seq data from 146 samples of 11 widely used fish cell lines were collected from public databases (NCBI‐SRA) and were mapped to the reference genomes of eight species. GCO RNA‐seq samples from three Chinese laboratories showed a mapping rate of 21.64% ± 3.61% to the grass carp genome, but 89.81% ± 4.83% to the fathead minnow genome. Further transcriptomic similarity analysis revealed that these GCO RNA‐seq samples clustered more closely with cell lines originating from fathead minnow. Targeted analysis of the COI gene amplification region confirmed that nearly all reads from GCO RNA‐seq samples mapped exclusively to the fathead minnow COI amplicon. Collectively, these results indicate that GCO may have undergone cross‐contamination or species misidentification. This study raises doubts about the true species origin of the GCO cell line and proposes that COI DNA barcoding can be used to discriminate the species origin of fish cell lines.

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Longitudinal multi-omics unveils rice-fish co-culture promotes common carp health and growth via microbiome remodeling - Chang Fang; Shi-jun Chen; Ke-ni Chen; Nian-nian Zhang; Bing Fu; Shu-ping Zhang; Si-yuan Xiong; Jia-en Zhang; Hui-rong Yang (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Engineering catalytic sites in ZnIn2S4 via Mg doping: A S-to-In shift toward enhanced photocatalytic H2 evolution - Yan Wang; Yuqi Shi; Xin Chong; Chao Wang; Rong Fu; Chang Liu; Yuelan Zhang (Chemical Engineering Journal, 2026)

Evolution Mechanism of Internal Swelling Induced by Gas Sorption of Coal Matrix: Theoretical Inversion and Numerical Simulation - Shouqing Lu; Yongfu Liu; Jiang Shi; Yujin Qin; Congmeng Hao; Zhanyou Sa; Jie Liu; Yongliang Zhang; Rong Zhang; Hao Zhang (Rock Mechanics and Rock Engineering, 2026)

Salinization-driven coupling of organic matter and phytoplankton in ice-covered lakes: Implications for carbon cycling - Shihuan Wang; Xiaohong Shi; Shengnan Zhao; Weiying Feng; Rong Wu; Fan Zhang; Sheng Zhang (Journal of Environmental Management, 2026)

Design, synthesis, biological evaluation, and computational studies of chalcone scaffolds as cholinesterase inhibitors - Xue-Wei Zhou; Yi-Xuan Wang; Wen-Rong Du; Chao-Yue Zhang; Shi-Hao Qin; Zheng-Yue Ma (Medicinal Chemistry Research, 2026)

Optimization of nitrogen-soil microbial interactions to regulate carbon and nitrogen footprints and enhance yield sustainability in maize fields - Tiantian Meng; Jingjing Shi; Xiangqian Zhang; Xiaoyu Zhao; Xiaorong Wu; Meiren Rong; Yanan Liu; Xingxing Guo; Shuli Wei; Yongfeng Ren; Zhanyuan Lu; Jianwei Zhang (Applied Soil Ecology, 2026)

Multidisciplinary modeling and dynamic Kriging assisted optimization for suborbital reusable launch vehicle - Teng Long; Haoda Li; Renhe Shi; Rong Chen; Baoshou Zhang; Nianhui Ye (Advances in Space Research, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Bidirectional electron transfer enabled by dual electric fields for efficient 4-nitrophenol removal on a bifunctional FeCoNiP/PCN heterojunction - Yan Wang; Chang Liu; Rong Fu; Chao Wang; Xin Chong; Yuqi Shi; Yuelan Zhang (Journal of Environmental Chemical Engineering, 2026)

Functional division of labor within defined yeast consortia drives flavor formation during early solid-state fermentation of sichuan shai vinegar - Jiajie Zhu; Yuting Liao; Yulin Zhao; Jun Liu; Zhicheng Li; Xiangpeng Kong; Suyi Zhang; Chuan Song; Qixu Fu; Xianbin Wang; Ruiqi Xue; Xuemei Shi; et al. (Food Microbiology, 2026)

Nitrogen application regulates ecosystem multifunctionality through soil microbial diversity: a quantitative assessment - Tiantian Meng; Yanan Liu; Xiangqian Zhang; Jingjing Shi; Xiaoyu Zhao; Xuanyi Chen; Meiren Rong; Xingxing Guo; Shuli Wei; Jiawei Liu; Zhanyuan Lu (Plant and Soil, 2026)

Spatial variations in soil carbon, nitrogen, and phosphorus stoichiometry across a northeast-southwest grassland transect in the monsoon-margin areas of China - Yuan Zhang; Na Rao; Bosen Yuan; Kai Wu; Xieping Xiang; Xumin Wei; Fangfang Xu; Jiusheng Ren; Yang Zhang; Ting Wu; Yun Zhang; Chao Huang; et al. (Journal of Soils and Sediments, 2026)

The influence of rewetting intensity on soil priming after drought - Yijin Lv; Rui Zhang; Rong Li; Zhenqing Shi (Applied Soil Ecology, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Pharmaceutical-dominated organic contaminants in plateau lakes: Suspect and non-target screening, PBT risk, and structure-based risk markers - Liben Chou; Wanshu Zhu; Rong Zhang; Jinsha Jin; Kai Huang; Lu Dong; Mengke Jin; Wenrui Luo; Yan Mao; Xiangyi Yu; Haoyue Tan; Jing Guo; et al. (Water Research, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Global patterns and soil controls governing terrestrial nitrogen cycling in response to experimental warming: A meta-analysis - Sen-Mao Zhang; Wan-Jia Hu; Xin-Rong Shi; Robert L. Kallenbach; Zhi-You Yuan (Soil Biology and Biochemistry, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Microbial-mediated nitrogen transformations alter N2O emissions at the scale of soil aggregates from abandoned farmlands - Rong Wang; Yixian Ruan; Runhao Shi; Sihan Wang; Yayun Yang; Bo Zhang; Linzi Lou; Hongjian Hao; Xinhui Han; Wei Zhang (Pedosphere, 2026)

Mechanism of macrophage mitochondrial transfer in CBNPs induced EndMT of pulmonary microvascular endothelial cells - Mengruo Wang; Qian Wang; Qingping Liu; Shanshan Zhang; Yujia Xie; Tao Zhang; Ze Yang; Lei Bao; Yaxian Pang; Dongxing Shi; Jiaji Cheng; Yujie Niu; et al. (Journal of Hazardous Materials, 2026)

Mechanism of synergistic astringency enhancement by organic acids in model wine: Insights from organic acid-phenols-protein triadic interaction - Yan Liu; Xiang Jie Jiang; Shi qing Zhang; Qing hao Zhao; Yue fan Zhao; Wan Rong Zhao; Shi Yi Peng; Guo Rong Du; Xiao Yuan; Peng Tao Zhao; Xiao Yu Wang (Food Chemistry, 2026)

A bioinspired integrated aerogel evaporator for ultra-high power and sustainable electricity generation - Yutong Huang; Denan Kong; Weitong Chen; Wenjie Dou; Ning Zhang; Rong Chen; Shengze Hu; Xu Han; Xianbao Wang; Quanzhen Zhang; Teng Zhang; Baofei Hou; et al. (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Engineering dual defects onto graphitic carbon nitride nanosheets enables outstanding performance for photodegradation of microcystin-LR - Ziqi Deng; Wenqing Zhang; Liangjie Shen; Lei Shi; Xiang Zheng; Jianzhong Zheng; Rong Cheng (Journal of Environmental Sciences, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Hydroxybutyl chitosan-based thermosensitive hydrogel enhanced osteoporotic bone regeneration through sustained release of alendronate and BMP-2 - Mingyuan Lei; Haibing Liu; Qiang Zhong; Libo Zhao; Jingwen Liu; Huaming Mai; Yuheng Zhang; Hongyu Wang; Yourong Chen; Rong Chen; Yixin Xu; Hao Li; et al. (Carbohydrate Polymers, 2026)

Research progress on the chemical composition changes of traditional Chinese medicine before and after processing based on modern analytical techniques - Xuelin Zong; Yun Shi; Ying Zhao; Yuman Li; Rong Guo; Gengyi Shang; Chenfeng Zhang; Jinyang Shen; Xun Gao; Weidong Li; Kunming Qin (Phytochemistry Reviews, 2026)

Identification of a novel selenium peptide from Oryzain α hydrolysate: Selenium-specific database establishment, sequence confirmation, and molecular interaction analysis - Xin Wang; Bailiang Xue; Rong Zhang; Lin Shi; Wei Jia (Food Bioscience, 2026)

Remediation of ternary heavy metal-polyethylene microplastics co-contaminated soil using co-modified biochar with deep eutectic solvent and warm patch: competitive interactions, mechanistic insights, and microbial community response - Luxin Zhang; Xiaobing Liu; Sishang Ge; Weiwei Shi; Rui Zhang; Chaoyang Li; Rong Chen (Environmental Research, 2026)

Effects and mechanisms of Klebsiella aerogenes HC10 on antimony accumulation in Brassica napus - Qian Zhang; Kai Zhong; Caiyuan Ling; Congyao Shi; Junyu Xiang; Zhongning Liu; Qun Rong; Chaolan Zhang (Applied Soil Ecology, 2026)

Synergizing machine learning and interpolation methods: A Stacking framework for global-scale satellite soil moisture gap filling - Jiaming Rong; Jiangyuan Zeng; Kun-Shan Chen; Hongliang Ma; Pengfei Shi; Husi Letu; Xiang Zhang; Xihui Gu; Haiyun Bi; Chunlin Zhang (Remote Sensing of Environment, 2025)

Screening, synthesis and anti-fatigue function verification of selenopeptides - Lin Shi; Wei Jia; Rong Zhang; Haizhen Mo (Food Research International, 2025)

Research on the fungi in dry-cured hams from different regions and exploration of new resources of flavor yeast - Wucong Zhou; Ai Zelin; Zilin Chen; Zhengyang Bao; Minxuan Shi; Chenghan Rong; Shuqing Yan; Xinzhu Zhang; Chunbao Li; Kai Shan (Food Research International, 2025)

Adulteration of animal-derived whey protein in infant formula: High-throughput screening of characteristic peptides - Lin Shi; Wei Jia; Rong Zhang; Xin Wang; Haizhen Mo (Food Research International, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Synergistic interfacial engineering and ion transport kinetics in high-safety PEO-based polymer electrolytes - Hong-Yu Wang; Kun-Rong Lu; Yue-Xi Han; Fa-Nian Shi; Peng-Fei Wang; Yu-Hang Zhang (Chemical Engineering Journal, 2025)

Carbon emissions from desert soil regulated by non-rainfall water inputs and their potential mechanisms - Xing Guo; Fan Du; Jungang Yang; Shihang Zhang; Kai Shi; Yongxing Lu; Xiaoying Rong; Jun Zhang; Rongliang Jia; Lu Gong; Yuanming Zhang; Xiaobing Zhou (CATENA, 2025)

Effects of Optimized Nitrogen Fertilizer Application on Chlorophyll Fluorescence Characteristics and Dry Matter Accumulation in Sugar Beet - Shi-Feng Dong; Lei Wei; Xing-Bo Tong; Yi-Na Zhang; Rong-Li Jia; Xu-Ming Xing; Shu-De Shi (Sugar Tech, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Multi-scale piezoresistive foam composed of graphene skeleton and vertical WS2 nanosheets designed for wearable detection/protection applications - Tengyue Song; Minxuan Xu; Yueqin Shi; Xin Li; Hang Wang; Zhe Kong; Suyu Sheng; Qi Zhang; Rong Xiang (Chemical Engineering Journal, 2025)

Exploring the dual role of anti-nutritional factors in soybeans: a comprehensive analysis of health risks and benefits - Dakai Di; Shudong He; Rong Zhang; Kuan Gao; Min Qiu; Xingjiang Li; Hanju Sun; Sophia Xue; John Shi (Critical Reviews in Food Science and Nutrition, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Hydroxyl Radical‐Driven Oxidation as a Key Pathway for Greenhouse Gas Production During Soil Drying–Rewetting - Xing Guo; Yongxing Lu; Jungang Yang; Fan Du; Yakov Kuzyakov; Yuanhe Yang; Shen Yu; Shuping Qin; Qinglong Fu; Xiaoying Rong; Benfeng Yin; Kai Shi; et al. (Global Change Biology, 2025)
The drying‐rewetting of soil can increase the release of greenhouse gases over a short time period and is one of the key pathways for greenhouse gas emissions in many terrestrial ecosystems, particularly in drylands. The mechanisms underlying this pulse of greenhouse gas emissions remain nearly unknown. Here, we conducted simulated soil rewetting experiments using typical cover of dryland soils (bareland, cyanobacteria/lichen‐covered soil, and moss‐covered soil). The 13 C, 15 N, and 18 O labeling techniques allowed to explore the intrinsic mechanisms of rapid carbon (C) and nitrogen (N) release from the soils following rewetting. We found that the hydroxyl radical (˙OH) was produced after soil rewetting via the rapid activation of microorganisms. The carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) production strongly decreased after ˙OH removal, whereas the methane (CH 4 ) production was not affected. The synergistic action between ˙OH oxidation and microbial enzymatic reactions increased CO 2 production. The ˙OH also stimulated the oxidation of NH 4 + to NO 3 − and dominated the N 2 O production. Our results confirm the role of ˙OH in the production of greenhouse gases and indicate that microbially mediated ˙OH oxidation mechanisms are an overlooked key pathway for the emission of greenhouse gases during the soil rewetting. In the context of climate change, the extreme weather‐induced drying‐rewetting cycles in soils are becoming more frequent, making greenhouse gas emissions via the ˙OH oxidation pathway increasingly important.

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Carbon black induced pulmonary fibrosis through piR-713551/PIWIL4 targeting THBS2 signal pathway - Mengruo Wang; Yong Niu; Qingping Liu; Peihao Yang; Mengqi Wu; Ruiting Wu; Beibei Shi; Jiawei Chen; Jingyuan Wang; Zhe Du; Yaxian Pang; Lei Bao; et al. (Journal of Environmental Sciences, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Implementation and topological characterization of Weyl exceptional rings in quantum-mechanical systems - Hao-Long Zhang; Pei-Rong Han; Xue-Jia Yu; Shou-Bang Yang; Jia-Hao Lü; Wen Ning; Fan Wu; Qi-Ping Su; Chui-Ping Yang; Zhen-Biao Yang; Shi-Biao Zheng (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Investigation into the bromination of polybrominated dibenzo-p-dioxins and dibenzofurans - Dan Li; Rong Cao; Haijun Zhang; Yun Fan; Mingyong Zhou; Haitao Shi; Jiping Chen (Journal of Hazardous Materials, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

Characteristics of nitrogen and phosphorus migration at sediment-water interface in seasonal frozen lakes and the mechanism of microbial driven cycling: a case study of Lake Daihai - Rong Wu; Xiaohong Shi; Xueer Kang; Sheng Zhang; Shengnan Zhao; Yu Liu; Biao Sun; Junping Lu; Haifeng Yu; Shihuan Wang; Xueru Pan; Kaiqi Shen; et al. (Journal of Contaminant Hydrology, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Type-A and -C response regulator genes positively impact rice plant height and panicle architecture - Chenyu Rong; Renren Zhang; Jing Xie; Jieru Li; Tiantian Yan; Ziyu Liu; Yuexin Liu; Ruihan Xu; Xi’an Shi; Xuebin Zhao; Jiali Song; Yayi Meng; et al. (Plant Cell Reports, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Global-scale gap filling of satellite soil moisture products: Methods and validation - Chunlin Zhang; Jiangyuan Zeng; Pengfei Shi; Hongliang Ma; Husi Letu; Xiang Zhang; Panshan Wang; Haiyun Bi; Jiaming Rong (Journal of Hydrology, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

The food application of a novel Staphylococcus aureus bacteriophage vB_SA_STAP152 and its endolysin LysP152 with high enzymatic activity under cold temperature - Yuanyu Li; Jingsha Dai; Shi Wu; Dongli Rong; Jiahui Huang; Miao Zhao; Jumei Zhang; Qinghua Ye; Qihui Gu; Youxiong Zhang; Xianhu Wei; Qingping Wu (Food Microbiology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Green recycling of end-of-life photovoltaic modules via deep-eutectic solvents – Part B - Yuelong Yu; Jianghao Shi; Xinjie Bai; Zhansheng Zhang; Fengshuo Xi; Shaoyuan Li; Jijun Lu; Wenhui Ma; Rong Deng (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Co-doping graphitic carbon nitride with Fe atoms and oxygen-containing functional groups for the efficient photo-Fenton degradation of sulfamethoxazole - Ruiyan Zhang; Cong Yan; Qinghua Yan; Congzhe Ren; Wen Zhang; Xiaozhe Song; Xuyang Li; Lei Chen; Fangyuan Zhou; Rong Xue; Feng Shi; Chongqing Xu (Journal of Water Process Engineering, 2025)

Comparative analysis of three extraction methods for ginger leaf polysaccharide: Chemical composition, antioxidant activity, and hypolipidemic effects - Zhong-hao Zhang; Zhong-hua Zhao; Tian-yi Cao; Cai-rong Yang; Zi-zhong Tang; Shi-ling Feng; Shu Yuan; Sheng-lin Hu; Ming Yuan (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Effect of myosin-kappa carrageenan pickering emulsions on the quality of bighead carp surimi gels - Zhongyang Ren; Xianglan Huang; Yongqiang Zhao; Linfan Shi; Shen Yang; Ritian Jin; Rong Lin; Shuji Liu; Zhiyu Liu; Yucang Zhang; Wuyin Weng (Food Hydrocolloids, 2025)

LibRPA: A software package for low-scaling first-principles calculations of random phase approximation electron correlation energy based on numerical atomic orbitals - Rong Shi; Min-Ye Zhang; Peize Lin; Lixin He; Xinguo Ren (Computer Physics Communications, 2025)

Air oxidation behavior of wet-mechanochemically synthesized pyrite FeS2: Fenton performance regulated by Fe species, sulfur vacancy and crystal facet ratio - Zunqing Wen; Xiaoguo Shi; Huiying Sui; Minglu Zhang; Longquan Zhang; Yawei Gu; Qing Feng; Ke Ma; Na Zhang; Mingzhe Wang; Ruiyan Zhang; Chongqing Xu; et al. (Chemical Engineering Journal, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Integrative deep learning framework predicts lipidomics-based investigation of preservatives on meat nutritional biomarkers and metabolic pathways - Wei Jia; Aiai Guo; Wenwen Bian; Rong Zhang; Xin Wang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Integrating larval zebrafish model and network pharmacology for screening and identification of edible herbs with therapeutic potential for MAFLD: A promising drug Smilax glabra Roxb. - Yinjuan Xiong; Xixuan Huang; Yuxin Li; Yukang Nie; Haodong Yu; Yaqi Shi; Jiajie Xue; Zhehui Ji; Keming Rong; Xuezhen Zhang (Food Chemistry, 2025)

Wind tunnel experiments on bioaerosol dispersion and exposure risk assessment in wastewater treatment plants under natural ventilation - Zhijian Liu; Chuanchen Li; Chenxing Hu; Rui Rong; Yaolong Shi; Zhijian Dong; Chenglin Ye; Chuang Zhang (Building and Environment, 2025)

Different contributions of microbial and plant residues to soil organic carbon accumulation during planted forest and abandoned farmland restoration, Loess Plateau, China - Hongjian Hao; Rong Wang; Shicai Li; Duo Pian; Ning Peng; Ahejiang Sailike; Zhouchang Yu; Jiayi Shi; Xingbo Wang; Zihan Wang; Wei Zhang (Plant and Soil, 2025)

Linker Histone H1.4 Inhibits the Growth, Migration and EMT Process of Non-Small Cell Lung Cancer by Regulating ERK1/2 Expression - Qian Chen; Mengqi Yang; Xinyue Duan; Jie Zhang; Fan Shi; Rong Chen; Yong Li (Biochemical Genetics, 2025)

Assessing the interaction of oceanic and riverine processes on coastal phytoplankton dynamics in the East China Sea - Jiawei Gao; Rong Bi; Julian P. Sachs; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Marine Life Science & Technology, 2025)
The interaction of riverine inputs and ocean current systems causes complex spatiotemporal variations in phytoplankton dynamics in marginal seas of the northwest Pacific Ocean, yet quantitative assessments of these variations and their causes remain limited. Here we evaluate phytoplankton biomass and community structure changes using lipid biomarkers, accompanying ocean circulation and nutrient variations in surface waters collected in spring and summer of 2017–2018 at 118 sites in the East China Sea off the Zhejiang coast. High biomass of diatoms, inferred from brassicasterol concentrations, shifted from the south in spring to the north in summer, while high dinoflagellate biomass, inferred from dinosterol concentrations, occurred mainly in the Changjiang (Yangtze) River plume and adjacent areas in both seasons. Seasonal variation in phytoplankton distribution was linked to the spatial extents of water masses such as the Changjiang Diluted Water (CDW) and the intrusion of the Kuroshio Subsurface Water (KSSW). A three end-member mixing model was applied to quantify water mass contributions. The results showed that an increase in the KSSW (from 0 to 40%) and a decrease in the CDW (from 100 to 20%) resulted in a significant (20%) increase in diatom proportions and a significant (20%) decrease in dinoflagellate proportions. Dinoflagellate proportions were highest in the CDW-dominated region, while diatoms and total phytoplankton biomass were higher in the CDW–KSSW mixing region and the KSSW-dominated region. This study highlights the dynamic response of the phytoplankton community to water mass changes in marginal seas that can aid coastal ecosystem management.

Isolation, structural elucidation and biosynthetic pathway of bioactive prenyl quinone compounds from Panus lecomtei based on untargeted metabolomics combined with molecular networking - Si-Xian Wang; Bao-Song Chen; Zi-Juan Zhang; Shi-Rong Zhu; Xiao-Ling Wang; Gao-Qiang Liu (Food Chemistry, 2025)

Ternary Ni:Fe- activated inert Cu-based electrocatalyst as efficient bifunctional electrocatalysts for water splitting - Shi-Yu Lu; Chunjie Wu; Tingting Hu; Ling Wang; Wenzhao Dou; Jun Zhang; Rong Wang; Yin Liu; Qian Yang; Zhigang Zou; Meng Jin (Chemical Engineering Journal, 2025)

High/Low-Index Faceted PdNi Alloy Nanocrystals as Highly Active and Stable Electrocatalyst for Oxygen Reduction - Jun Zhang; Xinlan Xu; Lanyu Luo; Tiantian Peng; Boyu Liu; Lingying Jiang; Meng Jin; Rong Wang; Huan Yi; Weimin Wu; Shi-Yu Lu (Chemical Engineering Journal, 2025)

Amelioration impact of gut-brain communication on obesity control by regulating gut microbiota composition through the ingestion of animal-plant-derived peptides and dietary fiber: can food reward effect as a hidden regulator? - Wei Jia; Jian Peng; Yan Zhang; Jiying Zhu; Xin Qiang; Rong Zhang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2024)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Cascading impacts of nitrogen deposition on soil microbiome and herbivore communities in desert steppes - Jingxi Liu; Mengmeng Zhu; Xiangfeng Shi; Cang Hui; Yurong Sun; Rong Zhang; Decai Jin; Zhihong Li; Honghao Chen; Zihua Zhao (Science of The Total Environment, 2024)

Occurrence and fate of atmospheric short/medium chain chlorinated paraffins: Size distribution and inhalation exposure - Naibing Liang; Rong Cao; Nan Jiang; Chengcheng Shi; Zhangpeng Guo; Yuan Gao; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Science of The Total Environment, 2024)

Strong electronic interaction in chromium-molybdenum dual incorporated few-layer cobalt sulfide nanosheets with lattice distortion for efficient bifunctional water splitting - Shi-Yu Lu; Wenzhao Dou; Chunjie Wu; Jun Zhang; Ling Wang; Tingting Hu; Rong Wang; Yin Liu; Qian Yang; Meng Jin (Fuel, 2024)

Novel Pickering emulsions using polysaccharide-myosin complexes: Effect of polysaccharide types - Zhongyang Ren; Xianglan Huang; Yongqiang Zhao; Linfan Shi; Shen Yang; Ritian Jin; Rong Lin; Shuji Liu; Zhiyu Liu; Yucang Zhang; Wuyin Weng (Food Hydrocolloids, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Assessment of carbon emissions and reduction potential in China's copper smelting industry - Rong Gao; Yao Shi; Chun Cao; Huiquan Li; Yuanbo Xie; Jingjing Shi; Chenmu Zhang; Xue Guan (Journal of Industrial Ecology, 2024)
As the largest producer and consumer of copper, China is facing enormous challenges from carbon peaking and neutrality. This article adopts “bottom‐up” and “top‐down” methods to construct a more accurate model, to predict the CO 2 emissions of China's copper smelting industry, and explores its potential for carbon reduction in the future from three scenarios as the baseline scenario (BAU), the general low‐carbon (NLC), and the enhanced low‐carbon (ELC). The results show that the CO 2 emissions can achieve a peak in 2028 either in NLC or ELC scenarios, with a peak range of 14.9–16.88 million tonnes. Prior to reaching the peak, the contributions of energy adjustment, material substitution, and process selection to carbon reduction have significantly improved, and the contribution rates increased from 30.91%, 4.11%, and 1.46% to 42.7%, 32.07%, and 15.63% in ELC scenario. After the peak, the contribution of energy adjustment gradually slows down, while the material substitution continues to increase, and the contribution rates increased from 21.25% and 32.07% to 29.38% and 40.01% in NLC and ELC scenarios. In the future, concentrate oxygen‐enriched bottom‐blowing smelting and direct refining from waste copper anode furnaces show ideal potential for carbon reduction before 2025, increasing the proportion of recycled copper production, and adjusting energy structure will be more effective from 2025 to 2035. The conclusions of this study can provide a scientific basis for formulating policy recommendations for green and low‐carbon development of the copper industry in China and all over the world in the future.

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Differential response of soil bacteria and fungi to carbon and respiration components in abandoned grasslands on the Loess Plateau, China - Xingfang Tian; Ying Zhang; Yujie Liang; Rong Fu; Lin Sun; Zhouchang Yu; Jiayi Shi; Ahejiang Sailike; Hongjian Hao; Wei Zhang (Plant and Soil, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Mining of novel target genes through Pan-genome analysis for Conventional PCR and Real-Time PCR detection of Staphylococcus argenteus in food - Jiahui Huang; Jingsha Dai; Ming Liu; Shixuan Huang; Yuwei Wu; Dongli Rong; Yuanyu Li; Miao Zhao; Ying Li; Jumei Zhang; Shi Wu; Qingping Wu (Food Control, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

Genetic variation in a heat shock transcription factor modulates cold tolerance in maize - Lei Gao; Lingling Pan; Yiting Shi; Rong Zeng; Minze Li; Zhuoyang Li; Xuan Zhang; Xiaoming Zhao; Xinru Gong; Wei Huang; Xiaohong Yang; Jinsheng Lai; et al. (Molecular Plant, 2024)

BBB-penetrating magnetoelectric nanoparticles with sustainable Gel formulation for enhanced chemotherapy and reduced postoperative glioma recurrence - Rong Huang; Chenteng Lin; Guangwei Jiang; Meng Zhang; Wenjia Gao; Kamiran Aihemaiti; Qianqian Liu; Jinlong Shi; Wei Shi; Rongqin Huang (Chemical Engineering Journal, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Soil Organic Matter and Amorphous Oxides Determine the Surface Electrochemical Properties of Purple Soil Under Long-Term Inorganic and Organic Fertilization - Jun Xie; Rong Huang; Dongxun Wu; Wencai Dai; Zhengxin Deng; Yue Li; Xiaojun Shi; Yueqiang Zhang; Zifang Wang; Ming Gao (Journal of Soil Science and Plant Nutrition, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Enhanced Fenton performance of wet-mechanochemically synthesized FeS2/Biochar: The multiple synergistic effect derived from mutual element doping - Zunqing Wen; Xiaoguo Shi; Yawei Gu; Ke Ma; Xiaozhe Song; Ao He; Chen Wang; Nianbo Zhang; Huiying Sui; Chongqing Xu; Rong Xue (Chemical Engineering Journal, 2024)

Molecular Cloning and Characterization of Scavenger Receptor Class B Type 1 in Grass Carp (Ctenopharyngodon idellus) and Its Expression Profile following Grass Carp Reovirus Challenge - Yang Zhang; Jiayuan Shi; Yuntao Lu; Qing Luo; Pengfei Chu; Rong Huang; Kunci Chen; Jian Zhao; Yaping Wang; Mi Ou (Fishes, 2024)
As a member of the pattern recognition receptor (PRR) class, scavenger receptor class B type 1 (SRB1) plays a key role in innate immunity. Grass carp (Ctenopharyngodon idellus) ranks among the most extensively cultivated freshwater aquaculture species in China. However, little is known about the function of SRB1 in C. idellus. In this research study, a SRB1 gene was identified in C. idellus, named CiSRB1. The full-length cDNA of CiSRB1 is 2486 bp long, with an open reading frame (ORF) of 2486 bp encoding a 497 amino acid (aa) protein containing a conserved CD36 domain. The identified genomic DNA length of CiSRB1 is 20,042 bp, including 12 exons and 11 introns. The predictive analysis of protein interactions revealed that CiSRB1 could interact with the outer capsid proteins of typical GCRV strains. The tissue distribution of CiSRB1 exhibited age-dependent characteristics. CiSRB1 displayed the highest expression in the intestines and moderate levels in muscle, spleen, liver, and brain of one-year-old grass carp while maintaining relatively low levels in three-year-old grass carp. Following grass carp reovirus (GCRV) infection, notable upregulation of CiSRB1 transcripts was observed in major immune tissues (gills, intestines, spleen, and liver). Furthermore, significant differences were found between one-year-old and three-year-old grass carp, with lower CiSRB1 expression levels being detected in the older group. Additionally, a distinct response to GCRV infection was observed in one-year-old and three-year-old grass carp. It was found that one-year-old individuals had a mortality rate of up to 84% 6 days post-infection (dpi), whereas all three-year-old counterparts survived after GCRV infection. The analysis of GCRV copy numbers across tissues revealed substantially higher levels in one-year-old grass carp compared with their older counterparts, confirming the existence of age-dependent susceptibility to GCRV infection in grass carp. Combined with these results, it was speculated that the decline in cell-surface CiSRB1 expression with age may impede reovirus binding to host cells, potentially explaining why older grass carp demonstrated enhanced resistance to GCRV infection. This observation accentuates the importance of CiSRB1 in the context of GCRV infection and provides insights into age-dependent susceptibility to reovirus.

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

Two-step synthesis of coconut shell biochar-based ternary composite to efficiently remove organic pollutants by photocatalytic degradation - Shipeng Zhang; Rong Wang; Jinhua Zhu; Xiaoyan Xie; Mei Luo; Hailong Peng; Yude Liu; Fei Feng; Ronghui Shi; Wang Yin (Journal of Environmental Chemical Engineering, 2024)

High-throughput analysis of hazards in novel food based on the density functional theory and multimodal deep learning - Lin Shi; Wei Jia; Rong Zhang; Zibian Fan; Wenwen Bian; Haizhen Mo (Food Chemistry, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

The interactions of subcellular organelles in pulmonary fibrosis induced by carbon black nanoparticles: a comprehensive review - Lei Bao; Qingping Liu; Jingyuan Wang; Lili Shi; Yaxian Pang; Yujie Niu; Rong Zhang (Archives of Toxicology, 2024)

Vertical distributions of lipid biomarkers in spring and summer in coastal regions of the East China Sea - Jiawei Gao; Shulan Xu; Rong Bi; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Frontiers in Marine Science, 2024)
Lipid biomarkers are amongst the most widely used proxies in studies of the structure and functioning of marine food webs. However, vertical distributions of lipid biomarkers and their controlling mechanisms remain unclear, especially in highly dynamic coastal ecosystems. Here we tested vertical profiles of key lipid biomarkers (sterols and fatty acids) in suspended particles and their correlations with water masses in spring of 2017 and summer of 2018 in the Zhejiang coasts of the East China Sea. The Changjiang Diluted Water, the Taiwan Strait Water and the Kuroshio Subsurface Water showed strong contributions in the surface layer in spring, the surface layer in summer, and the deep layer in both seasons, respectively. Accordingly, lipid biomarker composition also varied between different water layers. Overall, lipid biomarker concentrations in the surface layer were around 2 ~ 7 times higher than those in the deep layer, indicating high phytoplankton biomass in the surface layer. The ratio of docosahexaenoic acid to eicosapentaenoic acid was also higher in the surface layer, especially in the south of our study region, suggesting high nutritional quality of particulate organic matters in the surface layer. Significant correlations between the depth profiles of lipid biomarkers and water masses suggested the control of water masses on lipid biomarker production. The distribution patterns of lipid biomarkers in our study are consistent with previous findings on zooplankton grazing and fish larvae, highlighting the significance of lipid biomarkers as trophic markers to study food web structure and functioning in highly dynamic coasts.

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Excessive fluoride induces ovarian function impairment by regulating levels of ferroptosis in fluorosis women and ovarian granulosa cells - Nan Geng; Siyuan Dong; Pengpeng Xie; Yi Zhang; Rong Shi; Chen Chen; Zhao Xu; Qun Chen (Reproductive Toxicology, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

High-throughput analytical methodology of monoalkyl phthalate esters and the composite risk assessment with their parent phthalate esters in aquatic organisms and seawater - Qiang-Qiang Shi; Feng Xu; Tao Shen; Rong-Rong Zhang; Hua Liu; Ming-Ze Chen; Ai-Li Sun; Ze-Ming Zhang; Xi-Zhi Shi (Journal of Hazardous Materials, 2024)

A layered sodium-ion host O3-NaFe0.5Ti0.5O2 enables Na-free cathodes through offering extractable Na-ions - Qingyang Song; Peng Shi; Zhiqiang Guo; Peng Zhang; Yuanhang Li; Xiaohui Rong; Xiaoyan Wu; Shuyin Xu; Huican Mao; Yingchun Lyu; Chengjun Zhu (Chemical Engineering Journal, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Counteracting effects on ENSO induced by ocean chlorophyll interannual variability and tropical instability wave-scale perturbations in the tropical Pacific - Rong-Hua Zhang; Feng Tian; Qidong Shi; Xiujun Wang; Tongwen Wu (Science China Earth Sciences, 2024)

Association between short-term exposure to ambient air pollution and upper respiratory tract infection in Kunshan - Hua Wang; Guohua Qian; Jian Shi; Wenjie Lu; Yingchao Chen; Kun Fang; Yang Shen; Huan Rong; Xuanhua Huangfu; Yan Feng; Wei Zhang; Kexun Zhang (International Journal of Biometeorology, 2024)

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

Applicability evaluation of innovative simplified methods of slatted floor in pig houses – A CFD study - Fei Qi; Xuedong Zhao; Zhengxiang Shi; Li Rong; Guoqiang Zhang; Hao Li (Computers and Electronics in Agriculture, 2024)

Influence of drought intensity on soil carbon priming and its temperature sensitivity after rewetting - Rui Zhang; Rong Li; Jialiang Kuang; Zhenqing Shi (Science of The Total Environment, 2024)

Fabrication of compact zein-chondroitin sulfate nanocomplex by anti-solvent co-precipitation: Prevent degradation and regulate release of curcumin - Yufan Shi; Shuang Rong; Tingxian Guo; Ruyi Zhang; Duoxia Xu; Yahong Han; Fuguo Liu; Jiaqi Su; Hongxin Xu; Shuai Chen (Food Chemistry, 2024)

Adulteration of endogenous substances as a next challenge in dairy safety: High-throughput analysis of flavours in goat milk based on the molecular mechanism of flavouring components dynamic changes - Lin Shi; Wei Jia; Rong Zhang; Zibian Fan; Haizhen Mo (Trends in Food Science & Technology, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Prevalence and characterization of Staphylococcus aureus and Staphylococcus argenteus isolated from rice and flour products in Guangdong, China - Dongli Rong; Zhenjie Liu; Jiahui Huang; Feng Zhang; Qingping Wu; Jingsha Dai; Yuanyu Li; Miao Zhao; Qi Li; Jumei Zhang; Shi Wu (International Journal of Food Microbiology, 2023)

Exploring novel ANGICon-EIPs through ameliorated peptidomics techniques: Can deep learning strategies as a core breakthrough in peptide structure and function prediction? - Wei Jia; Jian Peng; Yan Zhang; Jiying Zhu; Xin Qiang; Rong Zhang; Lin Shi (Food Research International, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Projected Regional 1.50°C and 2.00°C Warming Threshold-crossing Time Worldwide Using the CMIP6 Models - Yali Meng; Keqin Duan; Wei Shang; Peihong Shi; Shuangshuang Li; Ying Cheng; Rong Chen; Zhaopeng Zhang (Chinese Geographical Science, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Associations of exposure to bisphenol A and its substitutes with neurodevelopmental outcomes among infants at 12 months of age: A cross-sectional study - Zhuanning Xia; Cheng Lv; Yan Zhang; Rong Shi; Qi Lu; Ying Tian; Xiaoning Lei; Yu Gao (Chemosphere, 2023)

Efficient capture of iodine by charge-induced effect of nitrogen-rich ionic liquids - Shi-Jie Guo; Guo-Hao Zhang; Qiu-Hong Zhu; Chao Yu; Jia-Ying Liu; Xiao-Lan Yang; Song Qin; Nan-Rong Zhao; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Fine mapping and candidate gene analysis of a novel fertility restorer gene for C-type cytoplasmic male sterility in maize (Zea mays L.) - Peng Zhang; Zhuofan Zhao; Mingmin Zheng; Yongming Liu; Qunkai Niu; Xiaowei Liu; Ziwen Shi; Hongyang Yi; Tao Yu; Tingzhao Rong; Moju Cao (Theoretical and Applied Genetics, 2023)

Characterization of nitrogen and phosphorus at the ice-water-sediment interface and the effect of their migration on overlying water quality in Daihai Lake (China) during the freezing period - Rong Wu; Yu Liu; Sheng Zhang; Xiaohong Shi; Shengnan Zhao; Junping Lu; Xueer Kang; Shihuan Wang; Yue Wu; Lauri Arvola (Science of The Total Environment, 2023)

The space-charge region at NiFe-MOF⊆LDH p-n junction by self-sacrificing LDH to boost oxygen evolution tandem with in-situ electro-Fenton - Na Zhang; Shi-Xian Guan; Qing Zhang; Jia-Rong Zhao; Jian-Yong Zhang; Qin-Fei Ke; Yong-Zheng Fang (Chemical Engineering Journal, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Fabrication of a novel antioxidant emulsifier through tuning the molecular interaction between soy protein isolates and young apple polyphenols - Zhi Chao Song; Huan Zhang; Peng Fei Niu; Lin Shan Shi; Xue Yan Yang; Yong Hong Meng; Xiao Yu Wang; Tian Gong; Yu Rong Guo (Food Chemistry, 2023)

How to improve pollutant emission performances of household biomass cookstoves: A review - Mengsi Deng; Pengxin Zhang; Yazhou Nie; Yu Shi; Hanyu Yang; Dan Wu; Xing Rong; Rongjiang Ma (Energy and Buildings, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

RETRACTED: Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2023)

Mechanisms and adsorption capacities of ball milled biomass fly ash/biochar composites for the adsorption of methylene blue dye from aqueous solution - Huaiyan Li; Jie Kong; Haiting Zhang; Jiale Gao; Yan Fang; Jiaqi Shi; Tao Ge; Ting Fang; Yanhong Shi; Rong Zhang; Ningyuan Zhang; Xinju Dong; et al. (Journal of Water Process Engineering, 2023)

Investigating the thermal conductivity and flame-retardant properties of BN/MoS2/PCNF composite film containing low BN and MoS2 nanosheets loading - Lei Yang; Wei Xu; Xiaolong Shi; Menglin Wu; Ziyi Yan; Qing Zheng; Gongneng Feng; Li Zhang; Rong Shao (Carbohydrate Polymers, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Quantum oscillations in field-induced correlated insulators of a moiré superlattice - Le Liu; Yanbang Chu; Guang Yang; Yalong Yuan; Fanfan Wu; Yiru Ji; Jinpeng Tian; Rong Yang; Kenji Watanabe; Takashi Taniguchi; Gen Long; Dongxia Shi; et al. (Science Bulletin, 2023)

Chemical weathering in the Himalayan system in response to the evolution of the Indian summer monsoon since 37 ka - Long Tan; Jianguo Liu; Yun Huang; Rong Xiang; Shengfa Liu; Hui Zhang; Jingrui Li; Linghui Yu; Xuefa Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Urinary neonicotinoid insecticides and adiposity measures among 7-year-old children in northern China: A cross-sectional study - Zhenping Lu; Yi Hu; Lap Ah Tse; Jinxia Yu; Zhuanning Xia; Xiaoning Lei; Yan Zhang; Rong Shi; Ying Tian; Yu Gao (International Journal of Hygiene and Environmental Health, 2023)

Engineering single-atom catalysts as multifunctional polysulfide and lithium regulators toward kinetically accelerated and durable lithium-sulfur batteries - Donghua Wang; Kaikai Ma; Jiamao Hao; Wenyuan Zhang; Haofeng Shi; Chengdeng Wang; Zhihao Xiong; Zhiming Bai; Fu-Rong Chen; Junjie Guo; Bingshe Xu; Xiaoqin Yan; et al. (Chemical Engineering Journal, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Detrital zircon age signatures of the basal Cambrian sandstone unit in North China: implications for drainage divides during global Sauk transgression and separation from Gondwanaland - Rong-Hao Wei; Liang Duan; Xingliang Zhang; Qing-Ren Meng; Rong-Ruo Zhan; Chu-Xuan Ma; Jing Xu; Yi Shi; Xiao-Yin Zhang (International Geology Review, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Nitrogen addition mediates monospecific and mixed litter decomposition in a boreal peatland - Xiong-Fei Zhang; Nan-Hai Zhong; Rui Li; Fu-Xi Shi; Rong Mao (CATENA, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

Lithologic control of soil C:N:P stoichiometry across a climatic gradient in southwest China - Mingming Sun; Rong Yang; Yixin Tang; Dan Xiao; Wei Zhang; Zhihong Xu; Zhihua Shi; Peilei Hu; Hanqing Wu; Kelin Wang (Journal of Soils and Sediments, 2023)

Identification of a novel eighteen-gene signature of recurrent metastasis neuroblastoma - Shufan Zhang; Rong Jiang; Manqiu Yang; Tao Wang; Hui Chen; Yifan Shi; Wei Liu; Moli Huang (Journal of Molecular Medicine, 2023)

Mechanism of natural antioxidants regulating advanced glycosylation end products of Maillard reaction - Wei Jia; Aiai Guo; Rong Zhang; Lin Shi (Food Chemistry, 2023)

Spinal cord astrocyte P2X7Rs mediate the inhibitory effect of electroacupuncture on visceral hypersensitivity of rat with irritable bowel syndrome - Zhi-jun Weng; Shi-xiu Hu; Fang Zhang; Zhi-ying Zhang; Yun Zhou; Min Zhao; Yan Huang; Yu-hu Xin; Huan-gan Wu; Hui-rong Liu (Purinergic Signalling, 2023)

Ancient DNA reveals potentially toxic cyanobacteria increasing with climate change - Jifeng Zhang; Kun Shi; Hans W. Paerl; Kathleen M. Rühland; Yanli Yuan; Rong Wang; Jie Chen; Mengjuan Ge; Lingling Zheng; Zhiping Zhang; Boqiang Qin; Jianbao Liu; et al. (Water Research, 2023)

The emergence of novel macrolide resistance island in Macrococcus caseolyticus and Staphylococcus aureus of food origin - Feng Zhang; Shi Wu; Jingsha Dai; Jiahui Huang; Jumei Zhang; Miao Zhao; Dongli Rong; Yuanyu Li; Juan Wang; Moutong Chen; Liang Xue; Yu Ding; et al. (International Journal of Food Microbiology, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

Alkali-catalyzed hydrothermal oxidation treatment of triclosan in soil: Mechanism, degradation pathway and toxicity evaluation - Yushuang Chen; Rui Shi; Hongjun Luo; Rong Zhang; Yafei Hu; Haijiao Xie; Neng-min Zhu (Science of The Total Environment, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

A study on molecular structural evolution of type II kerogen in a gold tube thermal system: Insights from solid-state 13C NMR - Deping Zhang; Huairen Cao; Yan Lei; Hao Wu; Xiaoyu Wang; Xuelian Guo; Jianping Yan; Shuhua Wang; Tianchi Shi; Haolin Li; Yan-rong Zou; Ping'an Peng (Fuel, 2023)

Preparation of Pinocembrin-Loaded F127/MPEG-PDLLA Polymer Micelles and Anti-Osteoporotic Activity - Xia Cao; Qing He; Michael Adu-Frimpong; Xinyi Shen; Wanjing Rong; Xiaoxiao Li; Jian Zhang; Xiaoli Xia; Feng Shi; Hao Ji; Elmurat Toreniyazov; Qilong Wang; et al. (AAPS PharmSciTech, 2022)

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

An improved hybrid bream derived from a hybrid lineage of Megalobrama amblycephala (♀)×Culter alburnus (♂) - Dingbin Gong; Min Tao; Lihui Xu; Fangzhou Hu; Zehong Wei; Shi Wang; Yude Wang; Qingfeng Liu; Chang Wu; Kaikun Luo; Chenchen Tang; Rong Zhou; et al. (Science China Life Sciences, 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Effect of water level on dynamic compaction in silty ground of Yellow River alluvial plain - Kai Yao; Yu Rong; Zhanyong Yao; Changyuan Shi; Chenjun Yang; Luchuan Chen; Baoshuo Zhang; Hongguang Jiang (Arabian Journal of Geosciences, 2022)

Three-dimensional numerical simulation of geothermal field in space—wavenumber domain - Dai Shi-Kun; Jia Jin-Rong; Qiang Jian-Ke; Chen Qing-Rui; Ling Jia-Xuan; Zhang Ying (Applied Geophysics, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Function identification of miR394 in tomato resistance to Phytophthora infestans - Yuan-Yuan Zhang; Yu-Hui Hong; Ya-Rong Liu; Jun Cui; Yu-Shi Luan (Plant Cell Reports, 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Retrospective surveillance of porcine circovirus 4 in pigs in Inner Mongolia, China, from 2016 to 2018 - Zhuo Ha; Chengdong Yu; Changzhan Xie; Guanyu Wang; Ying Zhang; Pengfei Hao; Jinfeng Li; Zhuoxin Li; Yanwei Li; Fulong Rong; Fulong Nan; He Zhang; et al. (Archives of Virology, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Dietary Supplementation with Sea Cucumber Saponins and Exercise Can Significantly Suppress Adipose Accumulation in Mice Fed with High-Fat Diet - Rong Li; Jing Meng; Haohao Shi; Chengcheng Wang; Zhaojie Li; Changhu Xue; Yuming Wang; Tiantian Zhang (Journal of Ocean University of China, 2021)

Chlamydia trachomatis induces autophagy by p62 in HeLa cell - Fuyan Wang; Hongbo Zhang; Xiaofang Lu; Quan Zhu; Tingting Shi; Rong Lu; Ping Yu; Lei Zhang; Yong Wang (World Journal of Microbiology and Biotechnology, 2021)

Flavonoids as key bioactive components of Oxytropis falcata bunge, a traditional anti-inflammatory and analgesic Tibetan medicine - Mei-Rong Zhang; Kan Jiang; Jun-Li Yang; Yan-Ping Shi (Natural Product Research, 2020)

Mapping quantitative trait loci associated with stem-related traits in maize (Zea mays L.) - Qiqi Shang; Degui Zhang; Rong Li; Kaixin Wang; Zimeng Cheng; Zhiqiang Zhou; Zhuanfang Hao; Jinbao Pan; Xinhai Li; Liyu Shi (Plant Molecular Biology, 2020)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Changes in leaf vein traits among vein types of alpine grassland plants on the Tibetan Plateau - Chang-shun Wang; Wang-wang Lyu; Li-li Jiang; Shi-ping Wang; Qi Wang; Fan-dong Meng; Li-rong Zhang (Journal of Mountain Science, 2020)

Effective identification of CRISPR/Cas9-induced and naturally occurred mutations in rice using a multiplex ligation-dependent probe amplification-based method - Sukumar Biswas; Rong Li; Jun Hong; Xiangxiang Zhao; Zheng Yuan; Dabing Zhang; Jianxin Shi (Theoretical and Applied Genetics, 2020)

Habitat fragmentation changes top‐down and bottom‐up controls of food webs - Rong Wang; Xin Zhang; Yi‐Su Shi; Yuan‐Yuan Li; Jianguo Wu; Fangliang He; Xiao‐Yong Chen (Ecology, 2020)
Top‐down and bottom‐up controls regulate the structure and stability of ecosystems, but their relative roles in terrestrial systems have been debated. Here we studied a hydro‐inundated land‐bridge system in subtropical China and tested the relative importance of these two controls in determining the rodent‐mediated regeneration of a locally dominant tree species. Our results showed that both controls operated in terrestrial habitats and that their relative importance switched as habitat size changed. Habitat loss initially removed predators of rodents that released rodent populations and triggered massive seed predation (top‐down control), leading to reduced seedling establishment. A further reduction in habitat size led to decrease in rodent population that was supposed to increase seedling survival of the tree species, but the decline in habitat size deteriorated the abiotic environments (bottom‐up control) that severely prevented seedling recruitment. As the ongoing global land use change is creating increasing number of small‐sized forest fragments, our findings provide novel insights into the restoration of seriously fragmented forests.

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Simulation of the landform change process on a purple soil slope due to tillage erosion and water erosion using UAV technology - Chao Yang; Zheng-an Su; Jian-rong Fan; Hai-dong Fang; Liang-tao Shi; Jian-hui Zhang; Zhou-yao He; Tao Zhou; Xiao-yi Wang (Journal of Mountain Science, 2020)

Stable Isotope Signatures and Moisture Transport of a Typical Heavy Precipitation Case in the Southern Tianshan Mountains - Liwei Wang; Mingjun Zhang; Shengjie Wang; Athanassios A. Argiriou; Gaofei Wang; Vasileios Salamalikis; Mengyu Shi; Rong Jiao (Chinese Geographical Science, 2020)

Prenatal exposure to organophosphate pesticides, maternal paraoxonase 1 genotype, and childhood neurodevelopment at 24 months of age in Shandong, China - Yiwen Wang; Yan Zhang; Lin Ji; Yijun Zhou; Rong Shi; Michihiro Kamijima; Jun Ueyama; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2020)

Effects of dietary hydroxyproline on collagen metabolism, proline 4-hydroxylase activity, and expression of related gene in swim bladder of juvenile Nibea diacanthus - Hua Rong; Yunlong Zhang; Meilin Hao; Weiguang Zou; Jun Yu; Chuanqi Yu; Qinchao Shi; Xiaobo Wen (Fish Physiology and Biochemistry, 2019)

Root diversity in sesame (Sesamum indicum L.): insights into the morphological, anatomical and gene expression profiles - Ruqi Su; Rong Zhou; Marie Ali Mmadi; Donghua Li; Lu Qin; Aili Liu; Jianqiang Wang; Yuan Gao; Mengyuan Wei; Lisong Shi; Ziming Wu; Jun You; et al. (Planta, 2019)

Proteomic responses to ocean acidification of the marine diazotroph Trichodesmium under iron-replete and iron-limited conditions - Futing Zhang; Haizheng Hong; Sven A. Kranz; Rong Shen; Wenfang Lin; Dalin Shi (Photosynthesis Research, 2019)

Uranium sorption onto mullite: Characteristics of isotherms, kinetics and thermodynamics - Liao Rong; Shi Zeming; Hou Yun; Zhang Kailiang; Zhang Junji; Wang Xinyu; Cheng Ke; Yang Lvhang (Journal of Earth System Science, 2019)

Identification and mapping of a photoperiod response gene (QPpd.zafu-4A) on wild emmer wheat (Triticum turgidum L.) chromosome 4AL - Jinsheng Yu; Yunzheng Miao; Siqing Yang; Zhaobin Shi; Nana Miao; Mingquan Ding; Hua Zhang; Yurong Jiang; Junkang Rong (Euphytica, 2019)

Four new dammarane-type triterpenes derivatives from hydrolyzate of total Gynostemma pentaphyllum saponins and their bioactivities - Xiaoshu Zhang; Guohui Shi; Mingbing Liu; Rong Chen; Xiaojun Wu; Yuqing Zhao (Natural Product Research, 2019)

Development of methods for effective identification of CRISPR/Cas9-induced indels in rice - Sukumar Biswas; Rong Li; Zheng Yuan; Dabing Zhang; Xiangxiang Zhao; Jianxin Shi (Plant Cell Reports, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Establishment and application of distant hybridization technology in fish - Shi Wang; Chenchen Tang; Min Tao; Qinbo Qin; Chun Zhang; Kaikun Luo; Rurong Zhao; Jing Wang; Li Ren; Jun Xiao; Fangzhou Hu; Rong Zhou; et al. (Science China Life Sciences, 2019)

Efficiency of maternal-fetal transfer of perfluoroalkyl and polyfluoroalkyl substances - Yiwen Wang; Wenchao Han; Caifeng Wang; Yijun Zhou; Rong Shi; Eva Cecilie Bonefeld-Jørgensen; Qian Yao; Tao Yuan; Yu Gao; Jun Zhang; Ying Tian (Environmental Science and Pollution Research, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Polybrominated diphenyl ethers in cord blood and perinatal outcomes from Laizhou Wan Birth Cohort, China - Limei Chen; Caifeng Wang; Yan Zhang; Yijun Zhou; Rong Shi; Chang Cui; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Spatial and temporal variation of soil organic carbon in the North China Plain - Rong Ma; Jiansheng Shi; Chao Zhang (Environmental Monitoring and Assessment, 2018)

The Effect of Bisphenol A on Growth, Morphology, Lipid Peroxidation, Antioxidant Enzyme Activity, and PS II in Cylindrospermopsis raciborskii and Scenedesmus quadricauda - Rong Xiang; Junqiong Shi; Yi Yu; Hongbo Zhang; Congcong Dong; Yanjun Yang; Zhongxing Wu (Archives of Environmental Contamination and Toxicology, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

EZH2 promotes cell proliferation by regulating the expression of RUNX3 in laryngeal carcinoma - Rong Lian; Huimin Ma; Zhiyan Wu; Guozheng Zhang; Lei Jiao; Wenjie Miao; Qianqian Jin; Ruixue Li; Ping Chen; Haixu Shi; Wenfa Yu (Molecular and Cellular Biochemistry, 2018)

Effect of spatial variability of engineering properties on stability of a CSMC embankment - Rong-Jun Zhang; Mohammed Shareef M. S. Hasan; Jun-Jie Zheng; Yu-Shi Cheng (Marine Georesources & Geotechnology, 2018)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Sleep and Cognitive Abnormalities in Acute Minor Thalamic Infarction - Wei Wu; Linyang Cui; Ying Fu; Qianqian Tian; Lei Liu; Xuan Zhang; Ning Du; Ying Chen; Zhijun Qiu; Yijun Song; Fu-Dong Shi; Rong Xue (Neuroscience Bulletin, 2016)

The effects of hairtail protein hydrolysate–Fe2+ complexes on growth and non-specific immune response of red swamp crayfish (Procambarus clarkii) - Bin Zhang; Zhou-rong Shi; Xiao-ling Wang; Shang-gui Deng (Aquaculture International, 2016)

Variation of hydraulic conductivity with depth in the North China plain - Rong Ma; Jiansheng Shi; Yilong Zhang; Lihui Sun (Arabian Journal of Geosciences, 2016)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

Prenatal low-level mercury exposure and infant neurodevelopment at 12 months in rural northern China - Yi Hu; Limei Chen; Caifeng Wang; Yijun Zhou; Yan Zhang; Yiwen Wang; Rong Shi; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2016)

Bacterial community dissimilarity between the surface and subsurface soils equals horizontal differences over several kilometers in the western Tibetan Plateau - Haiyan Chu; Huaibo Sun; Binu M. Tripathi; Jonathan M. Adams; Rong Huang; Yangjian Zhang; Yu Shi (Environmental Microbiology, 2016)
Summary Many studies have investigated patterns in the near‐surface soil microbial community over large spatial scales. However, less is known about variation in subsurface (15–30 cm of depth) microbial communities. Here we studied depth profiles of microbial communities in high‐elevation soils from Tibet. The relative abundance of Acidobacteria, Chloroflexi and Alphaproteobacteria was higher in near‐surface layers, while the relative abundance of Actinobacteria, Gemmatimonadetes and Betaproteobacteria was higher in the subsurface samples. The microbial community structure was distinct between the surface and subsurface soil layers, strongly correlating with variation in total carbon (TC) and carbon to nitrogen ratio (C/N). The differences in the microbial community between the layers were about the same as the horizontal differences between sites separated by many kilometers. Overall, we found that TC and C/N were the best predictors for both surface and subsurface microbial community distribution. Exploration of the relative contribution of distance and environmental variables to community composition suggests that the contemporary environment is the primary driver of microbial distribution in this region. Reflecting niche conservatism in evolution, the microbial communities in each soil site and layer tended to be more phylogenetically clustered than expected by chance, and surface soil layer samples were more likely to be clustered than subsurface samples.

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Effects of silica exposure on the cardiac and renal inflammatory and fibrotic response and the antagonistic role of interleukin-1 beta in C57BL/6 mice - Jiali Guo; Tingming Shi; Xiuqing Cui; Yi Rong; Ting Zhou; Zhihong Zhang; Yuewei Liu; Yan Shen; Weihong Chen (Archives of Toxicology, 2016)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Household pesticide exposure and the risk of childhood acute leukemia in Shanghai, China - Yan Zhang; Yu Gao; Rong Shi; Didi Chen; Xiaojin Wang; Michihiro Kamijima; Kiyoshi Sakai; Tamie Nakajima; Md. Khalequzzaman; Yijun Zhou; Ying Zheng; Pingping Bao; et al. (Environmental Science and Pollution Research, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

De novo analysis of the Tenebrio molitor (Coleoptera: Tenebrionidae) transcriptome and identification of putative glutathione S-transferase genes - Su Liu; Xiao-Xiao Shi; Yan-Dong Jiang; Zi-Jie Zhu; Ping Qian; Min-Jing Zhang; Hang Yu; Qing-Zi Zhu; Zhong-Jun Gong; Zeng-Rong Zhu (Applied Entomology and Zoology, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

Litter mass loss and nutrient dynamics of four emergent macrophytes during aerial decomposition in freshwater marshes of the Sanjiang plain, Northeast China - Xinhou Zhang; Changchun Song; Rong Mao; Guisheng Yang; Baoxian Tao; Fuxi Shi; Xiaoyan Zhu; Aixin Hou (Plant and Soil, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Determination of Pb genotoxic effects in Allium cepa root cells by fluorescent probe, microtubular immunofluorescence and comet assay - Ze Jiang; Rong Qin; Huanhuan Zhang; Jinhua Zou; Qiuyue Shi; Junran Wang; Wusheng Jiang; Donghua Liu (Plant and Soil, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

An improved wind speed algorithm for “Jason-1” altimeter under tropical cyclone conditions - Bangyong Qin; Xuan Zhou; Honglei Zhang; Xiaofeng Yang; Rong Lu; Yang Yu; Lijian Shi (Acta Oceanologica Sinica, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Optimization of Extraction and Purification of Arctiin from Fructus arctii and Its Protection Against Glucose-Induced Rat Aortic Endothelial Cell Injury - Lai-chun Lu; Rong Zhang; Ming-bao Song; Shi-wen Zhou; Gui-sheng Qian (Cell Biochemistry and Biophysics, 2014)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Transjugular intrahepatic portosystemic shunt induced short- and long-term cerebral blood flow variations in cirrhotic patients: an arterial spin labeling MRI study - Gang Zheng; Long Jiang Zhang; Yue Cao; Zhiying Pan; Rong Feng Qi; Ling Ni; Donghong Shi; Xinxin Fan; Guang Ming Lu (Metabolic Brain Disease, 2013)

Short-term effect of cultivation and crop rotation systems on soil quality indicators in a coastal newly reclaimed farming area - Rong-Jiang Yao; Jing-Song Yang; Tong-Juan Zhang; Peng Gao; Shi-Peng Yu; Xiang-Ping Wang (Journal of Soils and Sediments, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

Potential hepatotoxicity of geniposide, the major iridoid glycoside in dried ripe fruits of Gardenia jasminoides (Zhi-zi) - Yue Ding; Tong Zhang; Jian-sheng Tao; Li-ying Zhang; Jian-rong Shi; Guang Ji (Natural Product Research, 2013)

Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Keri Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Establishment of reference mandibular plane for anterior alveolar morphology evaluation using cone beam computed tomography - Rong-yang Wang; Min Han; Hong Liu; Chun-ling Wang; Hong-hong Xian; Lei Zhang; Shi-jie Zhang; Dong-xu Liu (Journal of Zhejiang University-SCIENCE B, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Recent developments in the detection of melamine - Yuan Liu; Ewen E. D. Todd; Qiang Zhang; Jiang-rong Shi; Xian-jin Liu (Journal of Zhejiang University-SCIENCE B, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Solid Lipid Nanoparticles Loaded with Anti-microRNA Oligonucleotides (AMOs) for Suppression of MicroRNA-21 Functions in Human Lung Cancer Cells - San-Jun Shi; Zhi-Rong Zhong; Jie Liu; Zhi-Rong Zhang; Xun Sun; Tao Gong (Pharmaceutical Research, 2012)

Protective effect of andrographolide against concanavalin A-induced liver injury - Guojun Shi; Zhijian Zhang; Rong Zhang; Xiaofang Zhang; Yan Lu; Jian Yang; Di Zhang; Zhiguo Zhang; Xiaoying Li; Guang Ning (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

Overexpression of a cytosolic glyceraldehyde-3-phosphate dehydrogenase gene OsGAPC3 confers salt tolerance in rice - Xiu-Hong Zhang; Xiao-Lan Rao; Hai-Tao Shi; Rong-Jun Li; Ying-Tang Lu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Halomonas qijiaojingensis sp. nov. and Halomonas flava sp. nov., two moderately halophilic bacteria isolated from a salt lake - Chao Chen; Rong Shi; Bing-Bing Liu; Yun-Jiao Zhang; Hong-Zhuan Sun; Chang-Tian Li; Shu-Kun Tang; Li-Li Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

LPS pretreatment ameliorates multiple organ injuries and improves survival in a murine model of polymicrobial sepsis - Dong-Wei Shi; Jing Zhang; Hong-Ni Jiang; Chao-Yang Tong; Guo-Rong Gu; Yuan Ji; Hanssa Summah; Jie-Ming Qu (Inflammation Research, 2011)

Overexpression of PGC-1β improves insulin sensitivity and mitochondrial function in 3T3-L1 adipocytes - Chun-Lin Gao; Guang-Ling Liu; Shi Liu; Xiao-Hui Chen; Chen-Bo Ji; Chun-Mei Zhang; Zheng-Kun Xia; Xi-rong Guo (Molecular and Cellular Biochemistry, 2011)

Molecular phylogenetic reconstruction of Osmanthus Lour. (Oleaceae) and related genera based on three chloroplast intergenic spacers - Shi-Quan Guo; Min Xiong; Chun-Feng Ji; Zhi-Rong Zhang; De-Zhu Li; Zhi-Yong Zhang (Plant Systematics and Evolution, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

Chemometrics-based approach to modeling quantitative composition-activity relationships for Radix Tinosporae - Shi-Kai Yan; Zhong-Ying Lin; Wei-Xing Dai; Qi-Rong Shi; Xiao-Hua Liu; Hui-Zi Jin; Wei-Dong Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Effects of exogenous putrescine on gas-exchange characteristics and chlorophyll fluorescence of NaCl-stressed cucumber seedlings - Run Hua Zhang; Jun Li; Shi Rong Guo; Takafumi Tezuka (Photosynthesis Research, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies - Jian-Ming Chen; Chen Gao; Qi Shi; Bing Shan; Yan-Jun Lei; Chen-Fang Dong; Run An; Gui-Rong Wang; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Archives of Virology, 2008)

Characterizing and estimating rice brown spot disease severity using stepwise regression, principal component regression and partial least-square regression - Zhan-yu Liu; Jing-feng Huang; Jing-jing Shi; Rong-xiang Tao; Wan Zhou; Li-li Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Mutation induced by ethylmethanesulphonate (EMS), in vitro screening for salt tolerance and plant regeneration of sweet potato (Ipomoea batatas L.) - Yu-Shi Luan; Juan Zhang; Xiao-Rong Gao; Li-Jia An (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

The style–length of the female florets and their fate in two dioecious species of Xishuangbanna, China - Zhang-Hong Shi; Da-Rong Yang; Yan-Qiong Peng (Trees, 2006)

Genetic Conservation of Hemagglutinin Gene of H9 Influenza Virus in Chicken Population in Mainland China - Jin-Hua liu; Katsunori Okazaki; Aaron Mweene; Wei-Min Shi; Qing-Min Wu; Jing-Liang Su; Guo-Zhong Zhang; Gui-Rong Bai; Hiroshi Kida (Virus Genes, 2004)

DNA extraction from archival formalin-fixed, paraffin-embedded tissues: heat-induced retrieval in alkaline solution - Shan-Rong Shi; Ram Datar; Cheng Liu; Lin Wu; Zina Zhang; Richard J. Cote; Clive R. Taylor (Histochemistry and Cell Biology, 2004)

Genetic analysis and breeding use of blast resistance in a japonica rice mutant R917 - Ming Xian Zhang; Jian Long Xu; Rong Ting Luo; De Shi; Zhi Kang Li (Euphytica, 2003)

ANALYSIS OF THREE MARINE FISH CELL LINES BY RAPD ASSAY - HUA-RONG GUO; SHI-CUI ZHANG; SHANG-LIANG TONG; JIAN-HAI XIANG (In Vitro Cellular & Developmental Biology - Animal, 2001)